Comparação genotípica e fenotípica de diferentes isolados clínicos de colonização e candidemia por Candida rugosa - Terçarioli, Gisela Ramos [UNIFESP] (2009)
Introduction: Candida rugosa is an emergent pathogen recognized by its higher occurrence in Latin American countries. This yeast has the ability to colonize and cause human bloodstream infections as well as to show resistance to several antifungal drugs, specifically to azoles. Objectives: To compare phenotypic properties such as virulence attributes and antifungal susceptibility, as well as to perform molecular identification and typing of C. rugosa clinical isolates obtained from patients who were either colonized or developed candidemia due to this species during the hospitalization period. We were also interested in evaluating such differences among strains isolated across two different periods: 1995/96 and 2001/02. Material and Methods: The strains were phenotypically characterized according to virulence factors, including the production of extra cellular enzymes (protease, phospholipase and lipase) and biofilm formation. We performed susceptibility testing to 5 antifungal drugs by using broth microdilution: amphotericin B, fluconazole, voriconazole, caspofungin and anidulafungin. To confirm identification to the species level and evaluate genetic variability, we have employed RAPD, microsatelite and rDNA ITS region sequencing. Results: Phenotypic properties varied considerably among the isolates, specifically regarding to hydrolytic enzymes production. Most of the isolates were low proteinase producers. The strains were phospholipase negative and showed a not very expressive biofilm formation in general. Nevertheless, lipase production was the only virulence factor considerably expressed by the clinical isolates, specifically by blood strains, suggesting the importance of this attribute in C. rugosa infection. The strains were sensitive to all the antifungal drugs tested, except fluconazole. The clinical isolates were highly related as determined by 3 different methods. However the control strain ATCC10571 was considered genotipically very different Our isolates were 90.5% similar among them and 87% similar to C. rugosa control strain as determined by RAPD, and 92% similar among them and 86,5% similar to ATCC10571, as determined by microsatelite. All the isolates were identified as C. rugosa by ITS region sequencing. The percentage of similarity ranged from 89% to 93% for the clinical isolates, and 99% to C. rugosa ATCC10571. Conclusions: It was not possible to establish a direct relationship between the expression of all virulence properties and patients clinical outcomes. However there is mounting evidence that lipase activity influences candidemia due to C. rugosa. It is possible that clonal dissemination in the hospital environment have occurred throughout several years. In addition, the genetic differences found between our isolates C. rugosa control strain ATCC10571, together with the phenotypic differences observed, such as higher biofilm formation and rough colony morphology, as well as low lipase activity for this control strain, suggest the genetic heterogeneity among the taxon C. rugosa.